2020
DOI: 10.1097/qad.0000000000002759
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of self-reported HIV-testing history and awareness of HIV-positive status in four sub-Saharan African countries

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
(19 reference statements)
1
16
0
Order By: Relevance
“…However, cross-validation of self-reported HIV testing histories with antiretroviral biomarker data from Eswatini, Malawi, Tanzania, and Zambia suggest that self-reported HIV testing history resulted in few false negatives. 31 Sixth, earlier estimates of diagnosis delays are informed by relatively few population-based survey estimates and HIV testing programme data. Given the cross-sectional nature of these metrics, they could be more sensitive to the elicited model's prior distributions in early years.…”
Section: Discussionmentioning
confidence: 99%
“…However, cross-validation of self-reported HIV testing histories with antiretroviral biomarker data from Eswatini, Malawi, Tanzania, and Zambia suggest that self-reported HIV testing history resulted in few false negatives. 31 Sixth, earlier estimates of diagnosis delays are informed by relatively few population-based survey estimates and HIV testing programme data. Given the cross-sectional nature of these metrics, they could be more sensitive to the elicited model's prior distributions in early years.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of status also remains lower among MSM than among all men living with HIV in Africa. However, knowledge of status may be underestimated since the majority of studies relied on self-reports, which are susceptible to underreporting 194,195 . This is particularly apparent when comparing our knowledge of status estimates with those from current ART coverage, which are roughly 10%-point higher.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the self-report of HIV testing and mediators. A study, however, showed that the sensitivity of self-reported HIV testing ranged from 96% to 99% with high specificity [43,44]. Despite this, reporting bias may still be present resulting to underreporting of sensitive information such as stigma.…”
Section: Discussionmentioning
confidence: 99%